RELEVANSI QAWA'ID AL-AHKAM DALAM PEMBENTUKAN HUKUM ISLAM KONTEMPORER - Safriani, Laela; Tenri Leleang, Andi; Musyahid, Achmad; Fatmawati (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
The death of the Prophet Muhammad (peace be upon him) essentially marked the end of revelation and the finalization of divine guidance for Muslims, as accumulated in the Qur'an and the Hadith. However, the complexity of social dynamics and contemporary developments demonstrate the need for adaptation and relevance of Islamic law to the contemporary context. In this context, the role of Qawā‘id al-Aḥkām (legal principles) is a fundamental element in efforts to understand and interpret Islamic law comprehensively. The focus of this study is to elaborate on Islamic legal principles and their implementation in order to provide innovative, sharia-guided solutions to new challenges, as well as to strengthen the philosophical foundation of contemporary ijtihad. The research method used is library research in normative legal studies with data sources from various books and research articles